The Thermoelectric Properties of Silver Doped of Lead Telluride - Lopyanko, M. A.; Mudri, S. I.; Optasyuk, S. V.; Semko, T. O.; Люба, Т. С.; Mateik, G. D.; Gorichok, I. V.; Jaworski, Ya. S. (Physics and Chemistry of Solid State, 2016)
The synthesis and study the structure and thermoelectric properties of silver doped of lead telluride with impurity concentration of 0.3, 0.5, 1.0 at.%. Established that in the samples PbTe: Ag with impurity concentration > 0.5 at. % Ag present phase pure lead, due to reaching the solubility of impurities. The influence of temperature of annealing on Seebeck coefficient, thermal conductivity and specific conductivity was identified.